Some Results of Fixed Point for Single Value Mapping in Fuzzy Normed Space with Applications - Sabri , Raghad I.; Ahmed , Buthainah A. A. (Iraqi Journal of Science, 2024)
Fixed point theory is not only essential in mathematics but also to a vast array of applications. In this approach, we provide some fixed point theorems for fuzzy normed space. The triangle property of a fuzzy norm is introduced first. This property is used to demonstrate some fixed point solutions for self-mappings in fuzzy normed space. To demonstrate the importance of the obtained results, an application for the existence of a solution to the ordinary differential equation and the Fredholm integral equation is constructed.